2022
DOI: 10.1007/s10750-021-04786-5
|View full text |Cite
|
Sign up to set email alerts
|

Extensive sampling sheds light on species-level diversity in Palearctic Placobdella (Annelida: Clitellata: Glossiphoniiformes)

Abstract: The bloodfeeding leech genus Placobdella is dominated by North American diversity, with only a single nominal species known from Central America and one from the Palearctic region. This is likely due to considerable underestimation of Palearctic biodiversity, but investigations into potential hidden diversity are lacking. To shed light on this, the present study introduces new data for specimens initially identified as Placobdella costata from Ukraine (close to the type locality),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 60 publications
2
19
0
Order By: Relevance
“…They were characterized by six distinct haplotypes, C8a to C8c in Morocco, C5a to C5c in Algeria, and C5a to C5b in Tunisia. According to the phylogenetic reconstruction shown in Figure 2 , P. costata sensu lato constitutes a robust clade that can be split into six distinct lineages, namely haploclades C1 + C7, C3, C4, C5, and C6 based on [ 39 ], and Haploclade C8 based on the present results. Conversely, due to technical difficulties in amplifying the COI of haemogregarines from blood samples, only 13 sequences were obtained from M. leprosa sampled from two localities of Morocco, from one locality of Algeria, and from two localities of Tunisia ( Table 3 ).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…They were characterized by six distinct haplotypes, C8a to C8c in Morocco, C5a to C5c in Algeria, and C5a to C5b in Tunisia. According to the phylogenetic reconstruction shown in Figure 2 , P. costata sensu lato constitutes a robust clade that can be split into six distinct lineages, namely haploclades C1 + C7, C3, C4, C5, and C6 based on [ 39 ], and Haploclade C8 based on the present results. Conversely, due to technical difficulties in amplifying the COI of haemogregarines from blood samples, only 13 sequences were obtained from M. leprosa sampled from two localities of Morocco, from one locality of Algeria, and from two localities of Tunisia ( Table 3 ).…”
Section: Resultsmentioning
confidence: 57%
“…While it is now well received from the investigation of molecular markers that Placobdella is a monophyletic genus, certain cryptic diversity was evidenced within several species, among which are Placobdella mexicana Moore 1898 and Placobdella ringueleti López-Jiménez and Oceguera-Figueroa 2009 [ 38 ]. Based on COI and ITS1 genetic variations, Kvist et al [ 39 ] also illustrated seven independent lineages within P. costata , suggesting at least five unique leech species across Central and Eastern Europe, as well as in Algeria. Independent phylogenetic relationships were shown among Italian populations of P. costata and their two host species E. orbicularis and E. trinacris [ 40 ]; thus, Kvist et al [ 39 ] concluded that species diversity and speciation within P. costata were likely not the result of speciation, isolation, or dispersal of the host species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, records of the latter (pond turtle-feeding) species north of the Arctic Circle are hardly expected. Based on genetically confirmed records, the northern portion of its range expands throughout northern Germany, Latvia, Ukraine, and Southern European Russia 45 . Briefly, the holotype (fixed by monotypy) of Placobdella raboti is a medium-sized ethanol-preserved specimen (body length 17 mm, body width 9.5 mm) of ovate shape, with small but deep posterior sucker (width 3 mm); proboscis pore opens on the rim of the anterior sucker (anterior lip); body thin, dorsal side convex, ventral side deeply concave; six rows of large dorsal papillae from somite XII to the last annuli, with marginal rows being smaller and less prominent; the edge of each a2 slightly rises apically, leading to a very particular scalloped aspect; body color uniformly grey-brown but with lighter ventral side and lighter dorsal papillae; one pair of eyespots; gonopores between two annuli; total number of annuli 67 13 .…”
Section: Taxonomic Accountmentioning
confidence: 99%
“…The composition of the mitogenome is relatively constant, comprising 13 protein-coding genes (PCGs), two ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and a control region (CR; (Wolstenholme 1992;Boore 1999). Therefore, because it has been so well characterized, mitochondrial DNA has been extensively employed for studying evolutionary genetics of animals, genetic structure and diversity of populations, molecular ecology, and species identification (Shen et al 2017;Besenbacher et al 2019;Su and Liang 2019;Shen et al 2020;Kvist et al 2022;Zuo et al 2022).…”
Section: Introductionmentioning
confidence: 99%